INTRODUCTION OF COMPLEMENTARY FOODS AND FOOD ALLERGIES: NEW STUDIES AND MODERN CLINICAL GUIDELINES - Leyla S. Namazova-Baranova; Elena A. Vishneva; Liliia R. Selimzianova; Svetlana G. Makarova; Anna A. Alekseeva ("Paediatrician" Publishers LLC, 2017)
The article is devoted  to the issues  of introducing  complementary  foods  as prevention  of atopy  and diet therapy in children with food allergy. Food sensibilization,  as a rule, is the initial link of allergy manifestations.  It represents  the first step of the so-called atopic  march,  followed  by  possible  development  of more  severe,  including  respiratory,  manifestations.  Considering  the  fact  that allergic diseases  are currently one of the most common pathologies with a growing tendency,  the correct choice of foods and the timely introduction of complementary foods are relevant, especially for children with hereditary tainted allergies. These products should be as safe as possible, should not cause sensibilization and at the same time should provide the child with the necessary macroand micronutrients. The publication provides an overview of the most relevant studies conducted in this field as well as a modern approach based on evidence-based  medicine and presented in the clinical guidelines on food allergy in children developed and approved by the professional association «Union of Pediatricians of Russia».